Practical experiences in implementing participatory budgets on examples of selected cities in Poland - Szmygin, Katarzyna; Górnik, Olga (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2020)
The article presents the idea of the participatory budget and the course of its subsequent editions in selected cities in Poland – Lublin and Olkusz. Since 2018, participatory budgets have been based on the binding law. For several years now, participatory budgets have played an important role in urban development policy in Poland and have been a part of the public debate on local development with the involvement of residents. The article describes selected parts of the 2018 Act and analyses the development of budgets in Lublin and Olkusz.